Riviu sistematis sikap guru terhadap pendidikan inklusif: Studi pada negara-negara berdasarkan kategori Human Development Index - Farida Kurniawati; Sulistami Prihandini (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2019)
Teachers’ attitude is an important factor that influences the quality of the implementation of inclusive education. The quality of inclusive education is part of the quality of education in general in a country. The quality of education of countries around the world is measured by the United Nations using the Human Development Index and placing countries in the very high, high, medium, and low categories. Systematic review was carried out to get an idea of ​​the attitudes of teachers towards inclusive education and the factors that influence it in countries based on the HDI category. By using three electronic search engines for academic data, namely EBSCOhost, ProQuest, and Taylor & Francis Online, 18 articles reporting teacher attitudes towards inclusive education in various countries were discussed. The results found that there were no differences in teacher attitudes towards inclusive education between countries with very high and high HDI categories with countries in the moderate HDI category. Knowledge of children with disabilities and teaching experiences of these children is known to influence the attitudes of teachers towards inclusive education in countries with all HDI categories. The support from community, the availability of professional assistance, and the length of the implementation of inclusive education are factors that influence the attitudes of teachers in very high and high HDI categories countries, while the negative perception of disability makes teachers held negative attitudes towards inclusive education. Recommendations for improving the review of this topic are discussed in this study